Micro Capsule with Functional Group for Diverse Application - Md Fazlul, Bari, Dr.; Kamaruddin, Husin, Brig. Jen. Dato' Prof. Dr.; Che Mohd Ruzaidi, Ghazali, Prof. Madya; Shamsul Baharin, Jamaludin, Prof. Dr. (Malaysian Invention & Design Society (MINDS), 2010)
Md Fazlul and his team won bronze for Micro Capsule with Functional Group for Diverse Application at 17th International Invention, Innovation & Technology Exhibition 2006 (ITEX 2006), 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC).